Internalizing Religious Values through Habituation: Strengthening Students’ Character in the Digital Era - Trisnantari, Hikmah Eva; Mutohar, Prim Masrokan; Jabbar, Moch. Rikza Alkhubra Abdul; Ismail, R. Ahmad (LETIGES, 2026)
This study aims to analyze the process of internalizing religious values through habituation-based practices and its contribution to the formation of students' religious character at SMP Islam Al Azhaar Tulungagung within the context of digital culture. This research is significant because the increasing use of social media and exposure to online content can influence students' moral orientations. In contrast, scholarly studies that explain an integrative model combining religious habituation with awareness of digital technology use in character education within Islamic schools remain limited. This study employed a qualitative case study design. Data were collected through in-depth interviews, participant observation, and documentation involving the school principal, teachers, and students. The data were analyzed using an interactive analysis model consisting of data condensation, data display, and conclusion drawing. The trustworthiness of the data was ensured through tests of credibility, transferability, dependability, and confirmability. The findings reveal that the internalization of religious values occurs through three interrelated stages: value transformation, value transaction, and value transinternalization. This study uses these three stages as a conceptual framework to explain the process of value internalization through religious habituation within the school culture. This process contributes to the development of students' religious character, which is reflected in disciplined worship practices, social concern, attitudes of tawadhu (humility) and politeness, as well as wisdom in the use of digital technology. This study is limited to a single case study conducted at a single educational institution; therefore, the findings cannot be generalized. Nevertheless, this research makes a conceptual contribution by proposing a framework for the internalization of religious values grounded in habituation and by opening opportunities for further research across diverse contexts of Islamic education.